Experimental investigation into the drag volume fraction correction term for gas-liquid bubbly flows. (12th October 2017) - McClure, Dale D.; Kavanagh, John M.; Fletcher, David F.; Barton, Geoffrey W.
Highlights: Volume fraction correction term measured at high superficial velocities. Value of the term was observed to depend on bubble size and bubble size distribution. New correlations for the volume fraction term have been developed. Abstract: Estimates have been made using data from an instrumented pilot-scale bubble column of the volume fraction correction term over a range of local volume fractions (0.03–0.38) and mean bubble diameters (4–10 mm) for Bubble Size Distributions (BSDs) of varying 'broadness'. The value of this correction term was found to depend on both the mean bubble diameter and the dispersity of the BSD, not simply on the local volume fraction. Using the available experimental data, no hindered bubble rise was observed. The results from this study should assist in the development of more accurate predictive CFD models of bubble columns and other gas-liquid systems operated at high local volume fractions.